Evaluación del impacto de la política de incentivos sectoriales en el desarrollo de los municipios mineros de Castilla y León - Berumen, Sergio A. (2012)
It is discussed whether the policy of incentives to the mining sector is or is not appropriate. Proponents argue that thanks to this the municipalities have greater opportunities to develop, while detractors argue that it makes no sense to channel resources into an industry without a future. In this paper we have proposed to evaluate the impact of the aid generated within the Coal Plan 1998-2005, the National Strategic Coal Reserve Plan 2006-2012, and the Structural Funds of the European Union 2000-2006 in twelve selected socioeconomic variables in the 105 municipalities of Castilla y León between 1998 and 2010. DOI: https://doi.org/10.1016/S2077-1886(12)70004-5